2004
DOI: 10.2337/diabetes.53.11.2861
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Link Between Skeletal Muscle Mitochondrial Efficiency and Age-Induced Insulin Resistance

Abstract: The transition from young to adult age is associated with decreased insulin sensitivity. To investigate whether changes in skeletal muscle mitochondrial function could be involved in the development of insulin resistance, we measured the oxidative capacity and energetic efficiency of subsarcolemmal and intermyofibrillar mitochondria isolated from the skeletal muscle of 60-and 180-day-old rats. Mitochondrial efficiency was tested by measuring the degree of thermodynamic coupling and optimal thermodynamic effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 40 publications
9
46
1
Order By: Relevance
“…For example, it was showed animals treated with R-etomoxir, an inhibitor of CPT-1, the key enzyme of intracellular fatty acid beta-oxidation, became more insulin resistant (Dobbins et al, 2001), while those with CPT-1 over-expression exhibited significantly increased insulin sensitivity (Perdomo et al, 2004). Aging is also associated with impaired intracellular fatty acid oxidation (Calles-Escandon et al, 1995, 1997Park et al, 2006), and this was proposed as an important mechanism underlying age-related insulin resistance (Petersen et al, 2003;Cree et al, 2004;Iossa et al, 2004;Menshikova et al, 2006;Slawik and Vidal-Puig, 2006). However, the mechanisms are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was showed animals treated with R-etomoxir, an inhibitor of CPT-1, the key enzyme of intracellular fatty acid beta-oxidation, became more insulin resistant (Dobbins et al, 2001), while those with CPT-1 over-expression exhibited significantly increased insulin sensitivity (Perdomo et al, 2004). Aging is also associated with impaired intracellular fatty acid oxidation (Calles-Escandon et al, 1995, 1997Park et al, 2006), and this was proposed as an important mechanism underlying age-related insulin resistance (Petersen et al, 2003;Cree et al, 2004;Iossa et al, 2004;Menshikova et al, 2006;Slawik and Vidal-Puig, 2006). However, the mechanisms are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have proposed that insufficient intracellular fatty acid oxidation and subnormal triglyceride (TG) accumulation in insulin target organs might be an important contributor (Cree et al, 2004;Iossa et al, 2004;Menshikova et al, 2006;Slawik and Vidal-Puig, 2006). Although the effects of aging on impaired fatty acid oxidation and fat accumulation have been well demonstrated in both humans and rodents (CallesEscandon et al, 1995(CallesEscandon et al, ,1997Park et al, 2006), the mechanism underlying is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, a significant direct relationship between skeletal muscle oxidative capacity and insulin sensitivity has been found. 54 In a previous work, we found a possible link between skeletal muscle mitochondria and insulin resistance in another obesity model, such as ageing, 32 and therefore it could be suggested that the alteration of mitochondrial function is a common cause of insulin resistance development in different obesity models. However, the underlying mechanisms appear to be different.…”
Section: Discussionmentioning
confidence: 99%
“…32 Mitochondrial oxygen consumption and membrane potential were titrated at 301C by sequential additions of malonate up to 3 mM for IMF and 5 mM for SS mitochondria. Measurements were carried out in a medium containing 30 mM LiCl, 6 mM MgCl 2 , 75 mM sucrose, 1 mM EDTA, 20 mM Tris-PO 4 , pH 7.0, succinate (10 mM), rotenone (3.75 mM), oligomycin (2 mg/ml), safranin O (83.3 nmol/mg), nigericin (80 ng/ml) and 0.1% (w/v) fatty acid free BSA.…”
mentioning
confidence: 99%
“…, and calibration curves made for each preparation as previously reported (18). Measurements were carried out at 30°C in a medium containing 30 mmol/l LiCl, 6 mmol/l MgCl 2 , 75 mmol/l sucrose, 1 mmol/l EDTA, 20 mmol/l Tris-P, pH 7.0, and 0.1% (wt/vol) BSA in the presence of succinate (10 mmol/l), rotenone (3.75 mol/l), oligomycin (2 g/ml), safranin O (83.3 nmol/mg), and nigericin (80 ng/ml).…”
Section: Methodsmentioning
confidence: 99%